Odpowiedzi

2010-01-26T19:51:30+01:00
A. x=1+y
3x=12

x=1+y
3(1+y)=12

x=1+y
3+3y=12

y=3
x=4

b.
5y=2/:2
x+y=2

y=0,4
x+ o,4=2

y=0,4
x=2-0,4

y=0,4
x=1,6

c. 4y-x=6
17y=0/:17

4y-x=6
x=0

4*0-x=6
y=0

0-x=6
y=0

-x=6/:(-1)
y=0

x=6
y=0

d a=b
2a+b=9

a=b
2b+b=9

a=b
3b=9/:3

a=b
b=3

a=3
b=3

e
11 3 11
2010-01-26T19:52:33+01:00
A) 3x=12
x=1-y

3( 1+y)=12
x=1-y
3+3x=12
x=1-y
3x=9
x=1-y
x=3
3=1-y
x=3
y=-2
12 2 12
Najlepsza Odpowiedź!
2010-01-26T23:30:43+01:00
A)
3x=12/:3
x-y=1

x=4
4-y=1

x=4
-y=1-4

x=4
-y=-3/:(-1)

x=4
y=3

b)
5y=2/:5
x+y=2⅖

y=0,4
x+0,4=2⅖

y=0,4
x=2⅖-0,4

y=0,4
x=2

c)
4y-x=6
17y=0/:17

-x=6-4y/:(-1)
y=0

x=-6+4y
y=0

x=-6+4*0
y=0

x=-6
y=0

d)
a=b
2a+b=9

a=b
2a+a=9

a=b
3a=9/:3

a=b
a=3

b=3
a=3

e)
u=4v
5u-v=10

u=4v
-v=10-5u/:(-1)

u=4v
v=-10+5u

u=4(-10+5u)
v=-10+5(4v)

u=-40+20u
v=-10+20v

u-20u=-40
v-20v=-10

-10u=-40/:(-10)
-10v=-10/:(-10)

u=4
v=1

f)
3r=s
3r+s=24

s=3r
3r=24-s/:3

s=3r
r=8-⅓s

s=3(8-⅓s)
r=8-⅓*3r

s=24-s
r=8-r

s+s=24
r+r=8

2s=24/:2
2r=8/:2

s=12
r=4


Mam nadzieję,że pomogłam...
Pozdrawiam:)





73 4 73